Monetary Policy Under EMU : Differences in the Transmission Mechanism? - Clements, Benedict (IMF Working Papers; Working Paper ;, 2001)
This study identifies differences in the monetary policy transmission mechanism across the countries in the euro area. It is argued that part of the differences in the response of economic activity to monetary policy during the pre-EMU period, found in other studies, reflected differences in monetary policy reaction functions, rather than different transmission mechanisms. In light of this, the paper constructs an empirical model on the basis of common reaction functions. The results confirm that even when a common monetary policy is implemented, its effects on economic activity are likely to differ across EMU countries. The paper also constructs an aggregate measure of the effect of monetary policy on prices and output. Finally, the paper examines the relative strength of the credit, exchange rate, and interest rate channels of monetary transmission in EMU countries.